Effect of different nanoparticle-dispersed nanofluids on hydrothermal-economic performance of minichannel heat sink - Kumar, V.; Sarkar, J. (Springer Netherlands, 2020)
Hydrothermal and energy-economic performances of minichannel heat sink are experimentally compared by using water-based different nanoparticle-dispersed mono and hybrid nanofluids. Al2O3, AlN, CNT, Cu and capric acid as phase change material (PCM) are considered. Different nanoparticles combinations (oxide–PCM, oxide–nitride, oxide–carbon nanotube and oxide–metal) in 50/50 volume ratio with water (base fluid) are taken as working fluids. The effects of volume flow rate (0.1–0.5 LPM) or Reynolds number (50 to 500) and total particle volume concentration (0.01–0.1%) are investigated. Convective heat transfer coefficient and pressure drop increase by about 42.3% and 22%, respectively, for Al2O3 + CNT nanofluid. The maximum reduction of 26.6% in thermal resistance is obtained for Al2O3 + CNT nanofluid as compared to base fluid. Heat transfer effectiveness and figure of merit are above one for all the hybrid nanofluids, which conclude that hybrid nanofluid is a better option over base fluid for minichannel heat sink. Al2O3 + CNT hybrid nanofluid is better in terms of heat transfer effectiveness, but Al2O3 + AlN hybrid nanofluid yields higher heat transfer coefficient to pressure drop ratio and coefficient of performance. The lower nanoparticle volume concentration in nanofluid is preferable due to higher stability, lower clogging and lower cost per cooling capacity of heat sink. © 2019, Akadémiai Kiadó, Budapest, Hungary.
Keywords: Minichannel heat sink; Hybrid nanofuid; Performance evaluation criteria; Unit cost; Experimentation; Coefcient of performance